Are You Feeding Your Hunger or Your Emotions?: The Truths about Weight Loss Nobody Ever Told You - Shikha Sharma (Wisdom Tree, 2015)
Do these combinations ring a bell? Are we all not guilty of feeding our emotions at some time or the other, if not mostly? Distilling and combining the best principles of Ayurvedic and New Age therapies, this book gives a wake-up call and asks a pertinent question, ‘Are you feeding your hunger, or your emotions?’ Honest, intelligent and written by one of the most respected Indian weight-loss therapists, it cuts through the clutter and helps you uncover the blind spot in weight-loss advice.